FRI0414 Can echocardiography replace follow-up cardiac catheterization in re-evaluation of pulmonary arterial hypertension? a longitudinal single-center study of 30 connective tissue disease patients. (15th June 2017) - Bournia, V-K; Tsangaris, I; Rallidis, L; Konstantonis, D; Anthi, A; Orfanos, S; Panopoulos, S; Sfikakis, PP
Abstract : Background: Transthoracic echocardiography (TTE) is well validated for initial assessment of connective tissue disease patients with suspected pulmonary arterial hypertension (PAH). However, in patients with PAH confirmed by the gold-standard method of right heart catheterization (RHC) the role of TTE in their follow-up is less known. Objectives: To test the hypothesis that TTE can replace follow-up RHC in connective tissue disease-associated PAH. Methods: This retrospective study included 30 consecutive patients with systemic sclerosis (n=24) and mixed connective tissue disease (n=6) (mean age±SD: 60±12 years, 87% women), in whom PAH was suggested by TTE and further confirmed by a baseline RHC [pulmonary artery systolic pressure (PASP): 56.8±19.1, range 25–90mmHg; pulmonary vascular resistance (PVR): 5.9±3.8, range 0.7–14.5 Wood units; cardiac output: 4.4±1.3, range 2–7.8 L/min). All 30 patients underwent a second RHC and TTE at follow-up, after 11±6 (range 4–29) months. Ten patients had a 3rd follow-up RHC and TTE 22±7 (range 15–37) months from baseline, thus producing in all 50 pairs of baseline and follow-up measurements. By considering follow-up RHC as the gold-standard, we examined whether clinically meaningful hemodynamic changes (i.e.>15% change from baseline) in either RHC-derived PASP or PVR could be predicted by the corresponding changes from baseline in follow-up TTE. RHC and TTE were always performed, each, by the same examiner. Results: In 68% of comparisons between baseline and follow-up, the latter TTE measurements could safely replace RHC in terms of PASP estimation. Using Mc Nemars test we confirmed that the two methods did not differ significantly (Table 1 ). When in addition to changes in PASP, PVR changes were also considered, follow-up TTE could again safely replace the second RHC in 70% patient retests (Table 2 ). Of note, baseline hemodynamic values or TTE measurements did not differ between patients in whom TTE could replace RHC and those in whom the results of the two methods at follow-up were divergent. Conclusions: In a study where operator-dependent methodological errors are limited we found that the majority of connective tissue disease patients with PAH can be safely monitored in the long-term by TTE. Further studies to help identify those patients at need for follow-up RHC are warranted. Disclosure of Interest: None declared